An Analysis of the Comparative Financial Performance of Sharia Banks and Conventional General Banks Based on the Banks Monetary Ratios from 2017 to 2019 - Ningsih, Sinta Anisa; Diana, Nana (Jurnal Ar-Ribh, 2023)
Sharia accounting that is an information system, is an effort that one of which is to deconstruct modern accounting in the form of humanist and the requirements of the values that feature the values of Islam. Sharia Accounting Information System has a major responsibility in moral problems. The method of analysis used is content analysis method is useful to know what is Sharia accounting. The goal of writing this study was to know the performance of the financial sharia and banks of conventional banks in the period 2017-2019 obtained from the financial statements of banks with the type of quantitative research. The population of the study of this research is the general bank of the conventional public sharia bank in the Indonesia Stock Exchange in the period of 2017-2019. The sample used in writing this research by Purpose Sampling method, and the sample used is Bank BRI and BRI Shariah, Bank BNI and BNI Syariah. Then there is a measuring tool for this research that is the basis of financial BOPO, ROE (Return On Equity), ROA (Return On Asset), NPL ( Non Performing Loan), LDR (Loan to Deposit Ratio) and CAR (Capital Adequacy Ratio).